Topoisomerase III Acts at the Replication Fork To Remove Precatenanes - Lee, Chong M. (J Bacteriol, 2019)
The role of DNA topoisomerase III (Topo III) in bacterial cells has proven elusive. Whereas eukaryotic Top IIIα homologs are clearly involved with homologs of the bacterial DNA helicase RecQ in unraveling double Holliday junctions, preventing crossover exchange of genetic information at unscheduled recombination intermediates, and Top IIIβ homologs have been shown to be involved in regulation of various mRNAs involved in neuronal function, there is little evidence for similar reactions in bacteria. Instead, most data point to Topo III playing a role supplemental to that of topoisomerase IV in unlinking daughter chromosomes during DNA replication. In support of this model, we show that Escherichia coli Topo III associates with the replication fork in vivo (likely via interactions with the single-stranded DNA-binding protein and the β clamp-loading DnaX complex of the DNA polymerase III holoenzyme), that the DnaX complex stimulates the ability of Topo III to unlink both catenated and precatenated DNA rings, and that ΔtopB cells show delayed and disorganized nucleoid segregation compared to that of wild-type cells. These data argue that Topo III normally assists topoisomerase IV in chromosome decatenation by removing excess positive topological linkages at or near the replication fork as they are converted into precatenanes. IMPORTANCE Topological entanglement between daughter chromosomes has to be reduced to exactly zero every time an E. coli cell divides. The enzymatic agents that accomplish this task are the topoisomerases. E. coli possesses four topoisomerases. It has been thought that topoisomerase IV is primarily responsible for unlinking the daughter chromosomes during DNA replication. We show here that topoisomerase III also plays a role in this process and is specifically localized to the replisome, the multiprotein machine that duplicates the cell’s genome, in order to do so.